Is task-shifting a solution to the health workers’ shortage in Northern Ghana? - Okyere, Eunice (PLoS One, 2017)
OBJECTIVE: To explore the experiences and perceptions of health workers and implementers of task-shifting in rural health facilities in Upper East Region, Ghana. METHODS: Data was collected through field interviews. A total of sixty eight (68) in-depth interviews were conducted with health workers’ in primary health care facilities (health centres); Four in-depth interviews with key persons involved in staff management was conducted to understand how task-shifting is organised including its strengths and challenges. The health workers interview guide was designed with the aim of getting data on official tasks of health workers, additional tasks assigned to them, how they perceive these tasks, and the challenges associated with the practice of task-shifting. FINDINGS: Task-shifting is a practice being used across the health facilities in the study area to help reduce the impact of insufficient health workers. Generally, health workers had a comprehensive training that supported the organisation of task-shifting. However, staff members’ are sometimes engaged in tasks above their level of training and beyond their actual job descriptions. Adequate training is usually not provided before additional tasks are assigned to staff members. Whilst some health workers perceived the additional tasks they performed as an opportunity to learn new skills, others described these as stressful and overburdening. CONCLUSION: Task-shifting has the potential to contribute to addressing the insufficient health workforce, and thereby improving health delivery system where the procedures are well defined and staff members work in a coordinated and organised manner. The provision of adequate training and supervision for health workers is important in order to improve their expertise before additional tasks are assigned to them so that the quality of care would not be compromised.